2019
DOI: 10.15393/j2.art.2019.4742
|View full text |Cite
|
Sign up to set email alerts
|

Strength and Elastic Modulus of Frozen Sandy Soil as a Material for a Logging Road

Abstract: The problem of forest roads improvement is relevant nowadays. The issues of strength of thawed and frozen soils as the materials of forest roads require further research. The article is aimed at the problem of developing a technique for indirect determination of elastic modulus and tensile stresses in frozen soil. It is based on the results of tests on three-point bending of a beam with a developing crack. The authors used methods of experimental and theoretical studies of mechanical systems. Testing was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…It can be assumed that the model ( 1)-( 18) is too simple to analyze such a complex object as a trabecular tissue, for which some transformation of the structure is possible [40,41] and changes in the interaction of structural elements during tension. The use of models with parameters [35,42] may be promising both for improving the results of the analysis and for expanding the scope of such models [43]. As can be seen, the model (16a) adequately reflects the trends of growth crease of apparent stresses at the stages before and after the point of the stress ex (Figure 10).…”
Section: Discussionmentioning
confidence: 96%
“…It can be assumed that the model ( 1)-( 18) is too simple to analyze such a complex object as a trabecular tissue, for which some transformation of the structure is possible [40,41] and changes in the interaction of structural elements during tension. The use of models with parameters [35,42] may be promising both for improving the results of the analysis and for expanding the scope of such models [43]. As can be seen, the model (16a) adequately reflects the trends of growth crease of apparent stresses at the stages before and after the point of the stress ex (Figure 10).…”
Section: Discussionmentioning
confidence: 96%
“…An elaborative model considering the particle breakage and its plastic shear mechanisms is established by Chang et al [24]. The shear strength and elastic modulus of frozen soil as studied by Khoroshilov et al [25], observed the shear strength parameters of frozen soil. Also, the in uence of freezing and thawing cycles on wind erosion strength of black soil simulations done by Liu et al [15].…”
Section: Introductionmentioning
confidence: 99%
“…An elaborative model considering the particle breakage and its plastic shear mechanisms is established by Chang et al [24]. The shear strength and elastic modulus of frozen soil as studied by Khoroshilov et al [25], observed the shear strength parameters of frozen soil. Also, the influence of freezing and thawing cycles on wind erosion strength of black soil simulations done by Liu et al [15].…”
Section: Introductionmentioning
confidence: 99%